Label-free optical biosensors in the pandemic era - Nava Giovanni; Zanchetta Giuliano; Giavazzi Fabio; Buscaglia Marco (Nanophotonics)
The research in the field of optical biosensors is continuously expanding, thanks both to the introduction of brand new technologies and the ingenious use of established methods. A new awareness on the potential societal impact of this research has arisen as a consequence of the Covid-19 pandemic. The availability of a new generation of analytical tools enabling a more accurate understanding of bio-molecular processes or the development of distributed diagnostic devices with improved performance is now in greater demand and more clearly envisioned, but not yet achieved. In this review, we focus on emerging innovation opportunities conveyed by label-free optical biosensors. We review the most recent innovations in label-free optical biosensor technology in consideration of their competitive potential in selected application areas. The operational simplicity implicit to label-free detection can be exploited in novel rapid and compact devices for distributed diagnostic applications. The adaptability to any molecular recognition or conformational process facilitates the integration of DNA nanostructures carrying novel functions. The high sensitivity to nanoscale objects stimulates the development of ultrasensitive systems down to digital detection of single molecular binding events enhanced by nanoparticles and direct enumeration of bio-nanoparticles like viruses.